Corrosion Inhibition Of Carbon Steel Xc70 In H2so4 Solution By Ferrocenederivative3- (ferrocenylmethylamine) benzonitrile - Zaiz, T.; Lanez, T. (University of Eloued جامعة الوادي, 2012)
In this work, we studied the efficiency of corrosion inhibition of carbon steel XC70 in H2SO4 0.5 M aqueous solution using ferrocenyl derivativessynthesized in our laboratory, this compound is: 3-(ferrocenylmethylamine)benzonitrile. The inhibitory potential of this compound was determined by electrochemical techniques based on Tafel segments. The results show that the studied compound has an efficiency of inhibition which depends on its concentration.The adsorption of these compounds on the surface of the metal is a chemical adsorption. The inhibition of corrosion reached 84 % at a concentration of 50 ppm.
Articale in Journal of fundamental and Applied Sciences Vol. 04 N. 02
Keywords: Corrosion, carbonsteelXC70, Inhibition,ferrocenederivative, Adsorption.